An oral history of Abraham Lincoln : John G. Nicolay's interviews and essays - Nicolay, John G. (John George), 1832-1901.; Burlingame, Michael, 1941- (Carbondale : Southern Illinois University Press, 1996)
"John G. Nicolay, who had known Lincoln in Springfield, Illinois, served as chief White House secretary from 1861 to 1865. Trained as a journalist, Nicolay had hoped to write a campaign biography of Lincoln in 1860, a desire that was thwarted when an obscure young writer named William Dean Howells got the job. Years later, however, Nicolay fulfilled his ambition; with John Hay, he spent the years from 1872 to 1890 writing a monumental ten-volume biography of Lincoln." "In preparation for this task, Nicolay interviewed men who had known Lincoln both during his years in Springfield and later when he became the president of the United States. "When it came time to write their massive biography, however," Burlingame notes, "he and Hay made sparing use of the interviews" because they had become "skeptical about human memory." Nicolay and Hay also feared that Robert Todd Lincoln might censor material that reflected "poorly on Lincoln or his wife."" "Nicolay had interviewed such Springfield friends as Lincoln's first two law partners, John Todd Stuart and Stephen T. Logan. At the Iillinois capital in June and July 1875, he talked to a number of others including Orville H. Browning, U.S. senator and Lincoln's close friend and adviser for over thirty-five years, and Ozias M. Hatch, Lincoln's political ally and Springfield neighbor. Four years later, he returned briefly and spoke with John W. Bunn, a young political "insider" from Springfield at the time Lincoln was elected president, and once again with Hatch." "Briefer and more narrowly focused than the Springfield interviews, the Washington interviews deal with the formation of Lincoln's cabinet, his relations with Congress, his behavior during the war, his humor, and his grief." "To supplement these interviews, Burlingame has included Nicolay's unpublished essays on Lincoln during the 1860 campaign and on Lincoln's journey from Springfield to Washington in 1861, essays based on firsthand testimony."--Jacket.
1. The Springfield Interviews -- Orville H. Browning -- John Todd Stuart -- Ozias M. Hatch -- Clark M. Smith -- William Butler -- Milton Hay -- Jesse K. Dubois -- Henry S. Greene -- Peter Van Bergen -- Stephen T. Logan -- John W. Bunn -- 2. The Washington Interviews -- James K. Moorhead -- Simon Cameron -- Norman B. Judd -- T. Lyle Dickey -- Hamilton Fish -- Lafayette Foster -- Lot M. Morrill -- William M. Evarts -- Ward Hill Lamon -- Leonard Swett -- Morton S. Wilkinson -- Stephen A. Hurlbut -- Lyman Trumbull -- John Palmer Usher -- Hannibal Hamlin -- Joseph Holt -- Richard M. Hoe -- John M. Sherman -- James Speed -- Godlove Orth -- Edward D. Neill -- Henry Wilson -- 3. Other Interviews and Two Essays by Nicolay -- Nathaniel P. Banks -- Dr. Parker -- Frederick W. Seward -- A Son of John W. Crisfield -- Robert Todd Lincoln -- John G. Nicolay -- William M. Springer -- "Lincoln in the Campaign of 1860" -- "Some Incidents in Lincoln's Journey from Springfield to Washington."
Includes bibliographical references (pages 123-158) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Lincoln, Abraham, -- 1809-1865 -- Friends and associates -- Interviews; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Friends and associates; Lincoln, Abraham, -- 1809-1865; Lincoln, Abraham, 1809-1865 -- Friends and associates; Lincoln, Abraham, 1809-1865.; HISTORY; Friendship; Interviews